Reduction of the P5A-ATPase Spf1p phosphoenzyme by a Ca2+-dependent phosphatase - Corradi, Gerardo Raul (2020)
P5 ATPases are eukaryotic pumps important for cellular metal ion, lipid and protein homeostasis; however, their transported substrate, if any, remains to be identified. Ca2+ was proposed to act as a ligand of P5 ATPases because it decreases the level of phosphoenzyme of the Spf1p P5A ATPase from Saccharomyces cerevisiae. Repeating previous purification protocols, we obtained a purified preparation of Spf1p that was close to homogeneity and exhibited ATP hydrolytic activity that was stimulated by the addition of CaCl2. Strikingly, a preparation of a catalytically dead mutant Spf1p (D487N) also exhibited Ca2+-dependent ATP hydrolytic activity. These results indicated that the Spf1p preparation contained a co-purifying protein capable of hydrolyzing ATP at a high rate. The activity was likely due to a phosphatase, since the protein i) was highly active when pNPP was used as substrate, ii) required Ca2+ or Zn2+ for activity, and iii) was strongly inhibited by molybdate, beryllium and other phosphatase substrates. Mass spectrometry identified the phosphatase Pho8p as a contaminant of the Spf1p preparation. Modification of the purification procedure led to a contaminant-free Spf1p preparation that was neither stimulated by Ca2+ nor inhibited by EGTA or molybdate. The phosphoenzyme levels of a contaminant-free Spf1p preparation were not affected by Ca2+. These results indicate that the reported effects of Ca2+ on Spf1p do not reflect the intrinsic properties of Spf1p but are mediated by the activity of the accompanying phosphatase.